2017
DOI: 10.1002/srin.201700247
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Aluminate Reactive Coatings on Carbon‐Bonded Alumina Filters for Clean Steel Approaches

Abstract: New carbon‐bonded filters with coatings based on calcium aluminates are developed. The samples are tested for 10 s in contact with a steel melt containing endogenous inclusions at 1650 °C, in order to explore the behavior and impact of these materials on the filtration process. Investigation of the filters after the test is carried out by optical and scanning electron microscopy. In addition, steel samples are analyzed with a special automatic SEM. The population of the detected inclusions is classified in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 16 publications
3
25
1
Order By: Relevance
“…The results of the ASPEX analysis on the steel samples are presented in Table and , where the detected inclusions are classified by size and chemistry, respectively. It is observed that the use of a filter had a mild impact on the total number of inclusions, compared with our previous investigations . Whereas the reference sample showed the maximum amount of inclusions within the 1–3 μm 2 size range, nanocoated filters presented the peak at 10–20 μm 2 .…”
Section: Resultscontrasting
confidence: 58%
“…The results of the ASPEX analysis on the steel samples are presented in Table and , where the detected inclusions are classified by size and chemistry, respectively. It is observed that the use of a filter had a mild impact on the total number of inclusions, compared with our previous investigations . Whereas the reference sample showed the maximum amount of inclusions within the 1–3 μm 2 size range, nanocoated filters presented the peak at 10–20 μm 2 .…”
Section: Resultscontrasting
confidence: 58%
“…Consequently, the structures most likely consist of calcium aluminates and/or alumina. Calcium aluminates were found to have a favorable behavior on the steel melt cleanliness when applied as filter coating . In the present case, calcium is present due to the gel‐casting procedure.…”
Section: Resultsmentioning
confidence: 65%
“…Summary of processes in a steel melt during active and reactive cleaning by ceramic foam filters, including a) principal scheme and examples of main reaction effects: b) oxide layer deposition on filter, c) NMIs adhesion on filter, d) agglomeration of NMIs in a steel melt …”
Section: Discussionmentioning
confidence: 99%
“…Coating abbreviations in Table denote alumina (Al 2 O 3 , “+A” coating), alumina‐based slurry (AC5, “+AC5” coating), carbon nanotubes and alumina nanosheets (CNT and ANS, “+Nano” coating) and calcium hexaluminate (CA6, “+CA6” coating). Detailed description on the coatings design, production, and properties are given elsewhere …”
Section: Methodsmentioning
confidence: 99%